Implementasi Kebijakan Remunerasi dalam Meningkatkan Kinerja Pegawai Negeri Sipil (PNS) di Fakultas Ilmu Sosial Universitas Negeri Malang - Al Hakim, Suparlan; Habibi, Muhammad Mujtaba; Sudirman, Sudirman (Jurnal Ilmiah Administrasi Publik, 2016)
The remuneration policy is a policy issued by the central government to give awards to civil servants on the professionalism of the work done. Remuneration is based on performance appraisal that is the target of employee and workplace behavior. This study aims to describe and analyze the implementation of the remuneration policy to improve the performance of civil servants at the Faculty of Social Sciences, State University of Malang, and to describe and analyze the factors that affect the implementation of the remuneration policy to improve the performance of civil servants at the Faculty of Social Sciences, State University of Malang. The results showed that the implementation of the remuneration policy at the Faculty of Social Sciences, State University of Malang can improve the performance of civil servants because the remuneration is based on the workload and responsibilities of employees. There are supporting factors and obstacles inthe implementation of remuneration policies that affect the policy implementation process.